Plasma and tissue disposition of danofloxacin in brown trout (Salmo trutta fario) after intravenous and intramuscular administrations - Corum, Orhan; Durna Corum, Duygu; Er, Ayse; Terzi, Ertugrul; Uney, Kamil (Informa UK Limited, 2018)
Plasma and muscle pharmacokinetics of danofloxacin were investigated after 10 mg/kg intravenous (IV, caudal vein) and intramuscular (IM, right epaxial muscles) administrations in 168 healthy brown trout (Salmo trutta fario) at 10°C-13°C. High-performance liquid chromatography was used to determine its plasma and muscle concentrations. Pharmacokinetic parameters were analysed with a non-compartmental model. After IV administration, elimination half-life (t1/2ʎz), area under the concentration-time curve (AUC0-∞), mean residence time (MRT0-∞), volume of distribution at steady state, total body clearance in plasma and AUCMuscle/AUCPlasma ratio were 22.22 h, 140.66 h*µg/mL, 23.15 h, 2.28 L/kg, 0.07 L/h/kg and 3.79, respectively. After IM administration, t1/2ʎz, AUC0-∞, MRT0-∞, peak concentration (Cmax), time to reach Cmax, bioavailability in plasma and AUCMuscle/AUCPlasma ratio were 28.28 h, 84.39 h*µg/mL, 37.31 h, 4.79 µg/mL, 1 h, 59.99% and 8.46, respectively. Danofloxacin exhibited long t1/2ʎz and good bioavailability after IM administration. Therefore, 10 mg/kg IM administration of danofloxacin in brown trout can provide AUC0-24/MIC of > 125 and Cmax/MIC of > 10 to treat diseases caused by susceptible bacteria with ≤ 0.336 µg/mL MIC.
Keywords: Trout; Muscles; Animals; Administration, Intravenous; Tissue Distribution; Injections, Intramuscular; Chromatography, High Pressure Liquid; Fluoroquinolones; 3. Good health